Steroid hormone receptors, exome sequencing and treatment responsiveness of breast cancer patient-derived xenografts originated in a South American country - Gabriela Pataccini; Andrés Elia; Gonzalo Sequeira; Luisa Ambrosio; Marcela Coianis; Caroline A. Lamb; Paola A. Rojas; Paula Martínez Vázquez; Javier Burruchaga; Eunice Spengler; Silvia I. Vanzulli; Martin Abba; et al. (Scientific Reports)
Abstract Breast cancer (BC) patient-derived xenografts (PDX) are relevant models for precision medicine. However, there are no collections derived from South American BC patients. Since ethnicity significantly impacts clinical outcomes, it is necessary to develop PDX models from different lineages. Our goals were to a) develop BC PDX from our population; b) characterize the expression of estrogen (ER), progesterone (PR), androgen (AR) and glucocorticoid (GR) receptors, basal and luminal cytokeratins, EGFR and HER2; c) identify PDX mutations; d) evaluate the response to treatments selected based on their biological and genetic features, and e) perform BC tissue cultures (BCTC) from PDX tissues and compare in vivo and ex vivo results. Surgical fragments were maintained in a culture medium and inoculated subcutaneously into untreated NSG female mice, or treated with estradiol pellets. Other fragments were fixed in formalin for diagnosis and immunohistochemistry, and a third piece was frozen at -80°C for molecular studies or whole exome-sequencing. Tumors were serially transplanted into NSG mice. Once the PDX was established, in vivo and ex vivo drug responses were evaluated. Eight PDX were established: two ER + [BC-AR685 (PR +) and BC-AR707 (PR-)], one from a triple-negative (TN) recurrence whose primary tumor was ER + (BC-AR485), one HER2 + (BC-AR474) and four TN primary tumors (BC-AR553, BC-AR546, BC-AR631 and BC-AR687). BC-AR685 had higher levels of PR isoform A than isoform B and was sensitive to mifepristone, tamoxifen, and palbociclib. BC-AR707 was inhibited by tamoxifen and testosterone. BC-AR474 was inhibited by trastuzumab and trastuzumab emtansine. BC-AR485 was sensitive to doxorubicin and resistant to paclitaxel in vivo and ex vivo. BC-AR687 carried a PIK3CA (C420R) mutation and was sensitive to alpelisib and mTOR inhibitors. All PDX expressed AR with varying intensities. GR and AR were co-expressed in the ER + tumors and in 3 TN PDX. We report the first PDX originated from South American countries that were genetically and biologically characterized and may be used in precision medicine studies. PDX expressing AR and/or GR are powerful tools to evaluate different endocrine treatment combinations even in TN tumors.